Triaquachlorido[3-dimethylamino-1-(2-pyridyl)prop-2-en-1-one-κN (1)]manganese(II) chloride - Chu, Zhao-Lian (International Union of Crystallography, 2009)
In the title compound, [MnCl(C(10)H(12)N(2)O)(H(2)O)(3)]Cl, the Mn(II) ion has a distorted octahedral coordination environment formed by one N and one O atom from the chelating 3-dimethylamino-1-(2-pyridyl)prop-2-en-1-one ligand, one chloride anion and three coordinated water molecules. Intermolecular O—H⋯O and O—H⋯Cl hydrogen bonds link the cations and anions into layers parallel to the ac plane.